Reasons and repercussions of pregnant women participation in operative group during prenatal care - Luana Carine Maron; Fernanda Beheregaray Cabral; Isabel Cristina Pacheco Van der Sand; Leila Mariza Hildebrandt (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210827 Aim: to identify the motivations of women-mothers and their relatives to join an operative group for pregnant women and the repercussions of their participation in this activity. Methods: it is a qualitative and descriptive research. The subjects of the study were selected among participants of operative groups in a city in the North of the state of Rio Grande do Sul, Brazil. The data were collected by semi-structured interviews and submitted to thematic analysis. Results: the reasons why the study subjects join an operative group can be summarized in little experience and difficulties related to maternity and its demands. The participation in the group emerged as a strategy to prepare for motherhood, make new friends, expand their interpersonal relations, build new social networks and make changes on lifestyle. Final considerations: the group consisted of a dialogue space, in which it was possible to exchange experiences and reflections on the care offer related to the birth process.